1988
DOI: 10.1067/mva.1988.avs0070108
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vein graft intimal thickening by eicosapentanoic acid: Reduced thromboxane production without change in lipoprotein levels or low-density lipoprotein receptor density

Abstract: Marine lipids containing omega-3 fatty acids (chiefly, eicosapentanoic acid [EPA] and docosahexanoic acid [DHA]) may inhibit the development of atherosclerotic vascular disease, but the mechanisms responsible for this putative beneficial effect are unknown. We investigated the effects of EPA and DHA in a canine model of accelerated vein graft arteriosclerosis during a 3-month period. Twenty-five dogs were divided into three dietary groups: group I (control), group II (2.5% cholesterol), and group III (2.5% cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Although it is an unlikely real-world scenario to include high levels of any one LC-PUFA, these observations and those of a previous study, confirm that there are no growth stimulatory effects owing to any individual LC-PUFA in juvenile barramundi (Glencross and Rutherford, 2011). In many species, EPA can exert cardio-protective benefits such as lowering triglycerides and low-density lipoprotein levels (Aarsland et al, 1990;Cahill et al, 1988;Cottin et al, 2011;Wei and Jacobson, 2011;Weiner et al, 1986). Whereas ARA on the other hand, is an essential and necessary precursor to the 2-series and 4-series eicosanoids that mediate homeostasis during times of environmental or physiological stress (Bell and Sargent, 2003).…”
Section: Discussionsupporting
confidence: 71%
“…Although it is an unlikely real-world scenario to include high levels of any one LC-PUFA, these observations and those of a previous study, confirm that there are no growth stimulatory effects owing to any individual LC-PUFA in juvenile barramundi (Glencross and Rutherford, 2011). In many species, EPA can exert cardio-protective benefits such as lowering triglycerides and low-density lipoprotein levels (Aarsland et al, 1990;Cahill et al, 1988;Cottin et al, 2011;Wei and Jacobson, 2011;Weiner et al, 1986). Whereas ARA on the other hand, is an essential and necessary precursor to the 2-series and 4-series eicosanoids that mediate homeostasis during times of environmental or physiological stress (Bell and Sargent, 2003).…”
Section: Discussionsupporting
confidence: 71%
“…Reiner et al reported a reduction of aortic atherosclerosis in mice with saturated fat diet supplemented with n-3 PUFA, and attributed it to the modulation of the expression and secretion of several macrophage effector molecules [7]. Other studies confirmed the reduction of atherogenesis in rodents and dog models of hypercholesterolemia or vascular injury subjected to fish oil rich diet, and highlighted the positive modulation of platelet function as a possible mechanism of action of n-3 PUFA [8][9][10][11].…”
supporting
confidence: 49%
“…Table 5 lists the studies exploring the effects of fish oil on allo-or autografted veins and arteries. The studies on arterialized venous [78][79][80] or synthetic [81] grafts are uniform in their outcome: fish oil reduces the extent of accelerated graft intimal proliferation, while not reducing the hypercholesteremia. All studies used dogs, added the fish oil as a supplement to the diet and measure intireal thickness of the graft or used a histologic grading system for intimal thickness, but only the dose of fish oil and the duration of the study varied.…”
Section: Animal Studies With Accelerated Graft-arteriosclerosismentioning
confidence: 99%
“…After 6 weeks graft intimal thickness of the non-treated hypercholesterolemic animals averages 39 ~Lm versus 24 txm (240 mg 20 : 5n-3/kg/day) and 23 ~Lm (480 mg 20 : 5n-3/ kg/day) in the fish oil treated groups [79], demonstrating the lack of dose-dependency. After 3 months graft intimal proliferation of the control group is markedly higher (125 ~m [80] and 143 ~Lm [78]) and the effect of fish oil somewhat greater (54% decrease [80] and 46% decrease [78]). In the study by Casali et al [81] no data on intimal thickening are presented, but the authors state that there was a significant reduction (p < 0.04) in the fish oil treated normocholesterolemic animals.…”
Section: Animal Studies With Accelerated Graft-arteriosclerosismentioning
confidence: 99%